Hyperlipidemia-induced cholesterol crystal production by endothelial cells promotes atherogenesis. Issue 1 (December 2017) - Baumer, Yvonne; McCurdy, Sara; Weatherby, Tina; Mehta, Nehal; Halbherr, Stefan; Halbherr, Pascal; Yamazaki, Noboru; Boisvert, William
Abstract Endothelial cells (EC) play a key role in atherosclerosis. Although EC are in constant contact with low density lipoproteins (LDL), how EC process LDL and whether this influences atherogenesis, is unclear. Here we show that EC take up and metabolize LDL, and when overburdened with intracellular cholesterol, generate cholesterol crystals (CC). The CC are deposited on the basolateral side, and compromise endothelial function. When hyperlipidemic mice are given a high fat diet, CC appear in aortic sinus within 1 week. Treatment with cAMP-enhancing agents, forskolin/rolipram (F/R), mitigates effects of CC on endothelial function by not only improving barrier function, but also inhibiting CC formation both in vitro and in vivo. A proof of principle study using F/R incorporated into liposomes, designed to target inflamed endothelium, shows reduced atherosclerosis and CC formation inApoE −/− mice. Our findings highlight an important mechanism by which EC contribute to atherogenesis under hyperlipidemic conditions. Atherosclerosis is characterized by subendothelial lipid retention believed to be the result of endothelial trancytosis. Here, the authors show that endothelium can take up and process LDL, generating cholesterol crystals that are deposited on the basolateral side of the cells, causing their dysfunction that can be prevented by forskolin/rolipram treatment.